Efeito do resveratrol nas alterações motoras e oxidativas induzidas por reserpina em camundongos - Busanello, Alcindo (2012)
Reserpine treatment is a putative animal model of orofacial dyskinesia, tremor, and Parkinsonism. Here, we examined the effects of resveratrol, a polyphenol with neuroprotective properties primarily contained in red grapes and red wine, in an animal model of vacuous chewing movements (VCM) induced by treatment with reserpine in mice. Mice were treated with reserpine (1 mg/kg, subcutaneously administered on days 1 and 3) and/or resveratrol (5 mg/kg, intraperitonealy administered 3 consecutive days). VCM, locomotor, and exploratory performance were evaluated. It was also analysed nonproteic thiol groups and Vitamin C levels in cortex and region containing both substantia nigra and striatum as antioxidant defense parameters. Reserpine treatment produced an increase in VCM intensity, which was significantly reduced by resveratrol co-treatment. Reserpine also decreased locomotor and exploratory activity in the open field test. However, resveratrol co-treatment was not able to protect against these effects. We did not find any statistical differences among the groups when antioxidant defense parameters were evaluated. The data suggest that resveratrol could be a promising pharmacological tool for treating VCM in rodents. However, further investigations are needed to understand the exact mechanisms involved in the neuroprotective effects of resveratrol.